2018
DOI: 10.1016/j.drudis.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of copper-64 radiopharmaceuticals as cancer theranostics

Abstract: Copper radionuclides are rapidly emerging as potential diagnostic and therapeutic tools in oncology, particularly Cu-radiopharmaceuticals for targeting neuroendocrine, prostate, and hypoxic tumors. Unexpectedly, experimental results are also revealing the impressive biological behavior of simple [Cu] ions. For example, it has been demonstrated that administration of ionic [Cu] in physiological solution allows the selective targeting of a variety of malignancies. These remarkable biological properties appear to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 95 publications
0
71
0
2
Order By: Relevance
“…Correspondingly, the ex vivo biodistribution data (Figure g) revealed a significant difference in uptake among the 64 Cu‐ l ‐G@SeNPs, 64 Cu‐ d ‐G@SeNPs, and 64 Cu‐ dl ‐G@SeNPs in the liver, spleen, pancreas, intestines, and kidney at 24 h p.i. In addition, for the nanosystem of either l ‐, d ‐, or dl ‐G@SeNPs, the chiral GSH, PC, and Se 2− (only in l ‐G@SeNPs) reduced some 64 Cu II to 64 Cu I , which disassociated from the nanoparticles in the form 64 Cu 2+ , which was quickly transported to the liver and eliminated through the bladder within 4 h, as demonstrated by the PET imaging.…”
Section: Resultsmentioning
confidence: 90%
“…Correspondingly, the ex vivo biodistribution data (Figure g) revealed a significant difference in uptake among the 64 Cu‐ l ‐G@SeNPs, 64 Cu‐ d ‐G@SeNPs, and 64 Cu‐ dl ‐G@SeNPs in the liver, spleen, pancreas, intestines, and kidney at 24 h p.i. In addition, for the nanosystem of either l ‐, d ‐, or dl ‐G@SeNPs, the chiral GSH, PC, and Se 2− (only in l ‐G@SeNPs) reduced some 64 Cu II to 64 Cu I , which disassociated from the nanoparticles in the form 64 Cu 2+ , which was quickly transported to the liver and eliminated through the bladder within 4 h, as demonstrated by the PET imaging.…”
Section: Resultsmentioning
confidence: 90%
“…Copper transporter 1 (CTR-1) is the major high-affinity copper transporter, which transports Cu(I) into the cells and deliver to the copper chaperone Cox17, the antioxidant protein 1 (Atox1), or the copper chaperone for superoxide dismutase (CCS). Atox1 further deliver copper to either the copper transporting adenosine triphosphatase (ATPase) ATP7A in neuron/astrocyte cells, or the ATPase ATP7B in the liver, which either pass the copper to target cuproenzymes, or to excretion [95][96][97][98][99]. Peng et al reported a significantly higher [ 64 Cu]CuCl 2 uptake in tumor tissue compared to normal tissue, meanwhile observing a substantial increase of CTR-1 expression in tumor but not in normal tissue [25].…”
Section: Copper Metabolismmentioning
confidence: 99%
“…In this case, the radioactivity coming from the radiopharmaceutical, carrying the diagnostic information outward from the body, is detected and transformed in a very precise picture of the radiopharmaceutical's distribution in the body by means of so-called "gamma cameras" working with sophisticated computerized algorithms. On the contrary, radionuclides decaying through the emission of massive particles, such as electrons or alphas, can be used in nuclear medicine for radionuclide therapy to treat certain types of cancer and other diseases [6][7][8].…”
Section: Introductionmentioning
confidence: 99%